COMMUNICATION PATTERNS IN CYBERCRIME (LOVE SCAMS CASE) - Christiany Juditha (Puslitbang Literasi dan Profesi SDM Komunikasi dan Informatika, 2015)
The development of information technology and communications gave rise to a new phenomenon as cybercrime. Based on the report of the State of The Internet in 2013 concluded that Indonesia has many records of crimes largest internet world and was second ranked the criminal case of cybercrime in the world’s. One of the most widely experienced cybercrime cases of Indonesian women is love scams (relationship of love by the internet). Communication patterns waged performer of cybercrime (scammers) who had known the victim was more credible than the direct communication of a person who has been known to be close. The purpose of this study was to describe the patterns of communication in the cybercrime. The method used is qualitative content analysis using Computer Mediated Communication (CMC) Models consisting of impersonal, interpersonal and hyperpesonal. This study concludes three patterns awoke in the case of love scams. The message source (scammers) have great control over they self and is in communication settings with the victims who did not know who they are. Because the scammers usually to convey the elements themselves are best personality, achievement, and appearance (photo)by internet channel. Message recipients (victims) who are lonely and looking for a mate usually flattered directly with messages of love and use feedback. Intense communication was established that the victim is tricked and lost hundreds of millions of rupiahs.Keywords: Communication patterns, cybercrime, love scams, scammers, Computer Mediated Communication (CMC).